ANALISIS KINERJA KEUANGAN PT GRAHAMAS CITRAWISATA TBK THE HILLS BUKITTINGGI HOTEL AND CONVENTION PERIODE 2009-2013 - Wanara, Anangga Dewang; Yuliana, Yuliana; Abrian, Youmil (Journal of Home Economics and Tourism, 2016)
The purpose of this study are to knowing financial performance PT. Grahamas Citrawisata Tbk 2009-2013 period from liquidity side, solvency side, activity side, profitability side of the company. The research consist of four indicators are: liquidity ratio, solvency ratio, activity ratio, profitability ratio. Kind of this research is descriptive quantitative, with the population is financies sheet who consist balance sheet, income statement sheet, cash flow sheet, capital statement sheet in PT. Grahamas Citrawisata Tbk’s annual report 2009-2013 period. The data used in this research is secondary’s data from directress PT. Grahamas Citrawisata Tbk. Base on the result clarify, financial performence of PT. Grahamas Citrawisata Tbk 2009-2013 period on bed condition from liquidity side caused by uneffective inventory managed. Financial performence from solvency side on bed conditioncaused by uneffectivefinancial leverage managed. Financial performence from activity sidecaused by uneffective asset utilization. Financial performence from profitability sidecaused by uneffective non-operating expense tackling. Key Words: liquidity ratio, solvency ratio, activity ratio, profitability ratio.1Prodi D4